Hungarian challenges of housing block regeneration: a case study of Uránváros, city of Pécs - András Trócsányi; Kristóf Orbán (Journal for Geography, 2012)
As post-socialist suburbanisation is about to decline, and the buildings of cities start to age rapidly, more and more attention is focused on city rehabilitation in East-Central Europe as well, which will probably be continued in the near future by the rehabilitation of early housing estates. Through an example, the current study shows the challenges such an action faces. Based on the comparison of demands with scenarios that were drawn up from data bases originating from a diverse methodology, it appears that the most reasonable idea would be to generally apply the basic principles of diversification and selecto-concentration, but the uniqueness of individual housing blocks requires that planning is done on an individual basis.